A Heterostructure‐In‐Built Multichambered Host Architecture Enabled by Topochemical Self‐Nitridation for Rechargeable Lithiated Silicon‐Polysulfide Full Battery (Adv. Funct. Mater. 41/2021). (7th October 2021) - Wei, Yunhong; Zhang, Mi; Yuan, Li; Wang, Boya; Wang, Hongmei; Wang, Qian; Zhang, Yun; Guo, Junling; Wu, Hao
Abstract : Lithiated Silicon Anodes In article number 2103456, Yun Zhang, Junling Guo, Hao Wu, and co‐workers report an intriguing "multistorey residential building"‐resembling multichambered nanofiber host architecture with an in‐built self‐nitridation generated TiN/TiO2 heterostructure, which favor the spatial accommodation of liquid Li2 S6 catholyte and their catalytic conversion, while ensuring the construction of rechargeable high‐energy‐density lithiated silicon‐polysulfide full batteries.